2021
DOI: 10.1053/j.ajkd.2021.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and Cellular Responses to mRNA-1273 and BNT162b2 SARS-CoV-2 Vaccines Administered to Hemodialysis Patients

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
120
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(137 citation statements)
references
References 47 publications
13
120
3
1
Order By: Relevance
“…Our findings of high antibody levels among MHD patients who recovered from COVID-19 correlate with previous studies of vaccinated MHD patients, [4,[8][9] J o u r n a l P r e -p r o o f and in the general population. In addition, a large study found sustained antibody levels in seropositive MHD patients, even without vaccination [10].…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings of high antibody levels among MHD patients who recovered from COVID-19 correlate with previous studies of vaccinated MHD patients, [4,[8][9] J o u r n a l P r e -p r o o f and in the general population. In addition, a large study found sustained antibody levels in seropositive MHD patients, even without vaccination [10].…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 90%
“…Previous studies reported high rates of early (14-30 days) seroconversion after BNT162b2, exceeding 90%. [2][3][4] While we suspect the lower rates in our study may result from decay of the humoral response over time, we cannot exclude that low antibody levels at 6 months post-vaccination represent weak initial vaccine responses. This distinction may prove critical to clarify when considering additional "booster" vaccine doses.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 81%
“…Current studies have mostly evaluated the effectiveness of vaccines in the form of IgG titers. However, studies involving the cellular responses or human leukocyte antigen are sparse and inconclusive [ 55 , 56 , 57 ]. Further studies should be undertaken to enhance the understanding of immune mechanisms following COVID-19 vaccination in patients with MHD.…”
Section: Effectiveness Of Covid-19 Vaccines In Hemodialysis Patientsmentioning
confidence: 99%
“…There are few studies that have addressed the cellular response to SARS-CoV-2 BNT162b2 mRNA vaccine in HD-patients [ 9 13 ]. In the ROMANOV study a decreased cellular response to the BNT162b2 vaccine was found [ 9 ].…”
Section: Introductionmentioning
confidence: 99%